2017
DOI: 10.1002/anie.201701572
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Functionalized Cyclopentene Derivatives from Vinyldiazo Compounds and Vinylazides through Sequential Copper‐Promoted [3+2] Cycloaddition/Azide Rearrangement

Abstract: Abstract:The reaction of vinylazides with alkenyldiazo compounds in the presence of [Cu(CH3CN)4][BF4] provided cyclopentene derivatives retaining the azide functionality. This process would involve a sequence comprising: 1) decomposition of the diazo component with generation of a copper alkenylcarbene species; 2) stepwise regioselective [3+2] cycloaddition; 3) allylic azide rearrangement. A broad range of substrates is compatible with this protocol. We have also shown that azide-containing cycloadducts can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…[11] Most commonly, vinyl azides produce vinyl nitrene intermediates by thermal decomposition or photolysis and thus act as a three atom CÀCÀN synthon in cycloaddition reactions. [13] Herein, for the first time we report the [4 + 2] cycloaddition reaction of ortho-quinone methides with vinyl azides for the synthesis of 4H-chromene derivatives. [13] Herein, for the first time we report the [4 + 2] cycloaddition reaction of ortho-quinone methides with vinyl azides for the synthesis of 4H-chromene derivatives.…”
mentioning
confidence: 99%
“…[11] Most commonly, vinyl azides produce vinyl nitrene intermediates by thermal decomposition or photolysis and thus act as a three atom CÀCÀN synthon in cycloaddition reactions. [13] Herein, for the first time we report the [4 + 2] cycloaddition reaction of ortho-quinone methides with vinyl azides for the synthesis of 4H-chromene derivatives. [13] Herein, for the first time we report the [4 + 2] cycloaddition reaction of ortho-quinone methides with vinyl azides for the synthesis of 4H-chromene derivatives.…”
mentioning
confidence: 99%
“…Our initial screening revealed that gold complexes (entries 1-3), which proved to be competent catalysts in several recent transformations involving stabilized vinyldiazo compounds, [5] failed to afford any coupling product in the reaction of 1a and 2a.Asimilar outcome was found when the reaction was performed in the presence of Rh 2 -(OAc) 4 or AgSbF 6 (entries 4a nd 5). Next, we evaluated as eries of copper complexes (entries [6][7][8][9][10][11]. It should be noted that although copper catalysts have been extensively studied in the decomposition of simple diazo compounds, their use in transformations involving vinyldiazo compounds is mainly restricted to enoldiazo acetates.…”
Section: Enol López and Luis A López*mentioning
confidence: 94%
“…Moreover,anX-ray structure analysis of cycloadduct 3j unambiguously confirmed the proposed structure. [9] Based on previous reports on metal-promoted transformations of vinyldiazo compounds,ap lausible mechanism for this transformation is depicted in Scheme 2. Initial reaction of the vinyldiazo compound with the copper(I) complex would form the copper(I) alkenylcarbene species I.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To date only a few reports available in the literature. For example, in 2017, López et al reported a Cu‐catalysed [3+2] cycloaddition/allylic azide rearrangement of vinyl carbene precursors with vinyl azide to form azidocyclopentenes (Figure a) . Very recently, Xu group reported Cu‐catalyzed asymmetric [4+2]‐cycloaddition of vinyl azides with unsaturated ketone esters to build various chiral cyclic azides (Figure b) .…”
Section: Introductionmentioning
confidence: 99%